Kinship Systems and Land Titling Dynamics: Gendered Land Governance in West and North Sumatra, Indonesia - Pujiriyani, Dwi Wulan; Mujiburohman, Dian Aries; Salim, M Nazir; Rineksi, Trisnanti Widi; Junarto, Rohmat (PALASTREN: Jurnal Studi Gender, 2026)
The gender imbalance in land ownership remains a major problem in agricultural governance, even in nations that have historically been regarded as more equitable towards women. Studies on matrilineal and patrilineal kinship systems focus on inheritance patterns. Still, they are inadequate in understanding the link between legal ownership, substantive control, and agricultural transition due to urbanisation and the land market. This article attempts to evaluate the role of kinship systems in determining the distribution of land ownership depending on gender and its consequences for land governance in West Sumatra and North Sumatra. The research employs a mixed-methods comparative study design with a qualitative ethnographic approach through an examination of land administration data, interviews, field observations, and documentation studies. Data collection was conducted in November 2025 through a 22-day field study in West Sumatra and North Sumatra. The article’s innovation is the application of a comparative agrarian-gender paradigm to understand the distinctions between symbolic ownership and substantive control in pluralistic kinship systems. The results suggest that matrilineal systems afford women greater administrative legitimacy, but not necessarily equal economic power, whereas patrilineal systems indicate stronger male dominance in agricultural management. These findings emphasise the necessity of more gender-responsive land governance through administrative reforms, the collection of gender-disaggregated agricultural data, and the enhancement of women’s participation in agrarian decision-making.